2005
DOI: 10.1002/mnfr.200400062
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A at nanomolar concentrations: A signal modulator in renal cells

Abstract: Ochratoxin A (OTA) is a ubiquitous fungal metabolite with nephrotoxic, carcinogenic, and apoptotic potential. Toxicokinetics make the kidney the primary target organ for OTA. Due to its widespread occurrence in improperly stored foodstuff the complete and safe avoidance of OTA for humans is impossible. There are several reports showing a significant correlation between OTA exposure and certain forms of nephropathies. At nanomolar concentrations OTA leads to specific changes of function and phenotype in renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 87 publications
(101 reference statements)
5
63
0
Order By: Relevance
“…A review of OTA on renal cells has indicated that glomerular capillaries are damaged by hypertension 38 , which is thought to contribute to OTA-induced disorders. PPARs are closely related to energy status and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A review of OTA on renal cells has indicated that glomerular capillaries are damaged by hypertension 38 , which is thought to contribute to OTA-induced disorders. PPARs are closely related to energy status and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nephrotoxicity is a consequence of acute, sub-acute, but also chronic exposure to OTA. Moreover, exposure to low OTA doses initiates nephrotoxicity (Gekle et al 2005). In this regard, chronic exposure (even to low doses) of OTA seems to be a significant public health problem (Malir et al 2013a).…”
mentioning
confidence: 99%
“…According to the European survey conducted by Miraglia et al (2), mean plasma concentration of OTA in adults is 0.875 nmol L -1 , and ranges from 0.53 nmol L -1 to 2.75 nmol L -1 . OTA half-life in serum ranges from 120 h in rats to 840 h in monkeys and humans (4,5). This prolonged retention in serum is the consequence of strong binding to serum proteins, mainly to albumin.…”
Section: Ochratoxin A: a Hazardous Mycotoxinmentioning
confidence: 99%